Indonesia Economic Quarterly, December 2012 : Policies in Focus - World Bank (World Bank, Washington, DC, 2018)
Indonesia's real Gross Domestic Product (GDP) growth has proven robust to the weakness in external demand in 2012. Real GDP rose by 6.2 percent year-on-year in the third quarter. This was slightly lower than the 6.4 percent growth seen in the second quarter and was the eighth consecutive quarter of above 6 percent growth. On a seasonally-adjusted quarter-on quarter basis the economy grew by 1.3 per cent in the third quarter, down from 1.6 percent in the second quarter. While real GDP growth eased only slightly, nominal GDP growth slowed significantly in the third quarter, falling to 9.9 per cent year-on-year, from 12.5 percent year-on-year in the second quarter. The level of investment spending remained high, up 10 percent year-on-year in the third quarter. However, investment did contract in seasonally adjusted quarter on quarter terms by 0.4 percent. This sequential contraction was largely driven by falls in spending on foreign transportation, machinery and equipment, consistent with the weakness in capital goods imports seen in the quarter. In contrast to the sharp drop in government consumption and moderation in investment, private consumption growth picked up in the third quarter, increasing by 5.7 percent year on-year. Growth in the services sectors moderated somewhat but was still solid at 7.3 percent year-on-year, compared to 8.1 year-on-year in the second quarter. Communications and transport remained one of the strongest of the service sectors (up 10.5 per cent year-on year). There was some moderation in the trade, hotel and restaurant sector in the quarter.